Adinegoro Pelopor Perjuangan Pena - Syela Joe Dhesita (Keraton: Journal of History Education and Culture, 2021)
Journalism has an important role in the development of Indonesian history. Its existence has become one of the tools of struggle as well. From the Dutch colonial era to the reform era, writings and journalists never miss taking a role. There are many journalists' names that also color the black and white long notes of Indonesia.  One of them adinegoro his work is considered to be the pioneer of Indonesian journalism.Born Djamaluddin was born in Talawi, Sawahlunto, West Sumatra on August 14, 1904 and died in Jakarta, January 7, 1967. Landjumin Tumenggung, the caretaker of Tjahaja Hinia magazine, was the one who suggested to Djamaluddin using the pseudonym Adinegoro. The point is that his essay can attract readers from Java. It turns out that later this pseudonym is much more popular than the actual name. Therefore, he became known as Djamaluddin Adinegoro. For his great service and work for Indonesia, his name is now enshrined as the highest award for Indonesian journalistic work, often known as Adinegoro Award  or Anugrah Adinegoro.